Strategy of Organik Agriculture Development in West Sumatra - Herri Myzani Myzani; Eri Barlian; Iswandi Umar (Science and Environmental Journal for Postgraduate, 2023)
This study reviews the development of organic farming, especially in the paddy field sector, since the introduction of Organic Agriculture Certification (SPO) in 2010. The method used The research was conducted using a qualitative approach and using the Interpretative Structural Modeling (ISM) method, while the population used for the research is in the areas of Agam Regency and Padang Pariaman Regency, West Sumatra as well as a sample of farmer groups/individual farmers in Agam Regency and Padang Pariaman Regency who have obtained SPO certification. The results of an analysis of organic farming in Agam Regency and Padang Pariaman Regency, West Sumatra, focus on paddy fields for several farmer groups that have been certified until 2023. This study details the growth of organic farming in West Sumatra and strategies to support sustainability in the region. Efforts such as SLAPO, PPO, and organic certification are supported by the Organic Task Force and LSO. The strategy analysis involved coordination between Provincial and Regency governments, strengthening farmer groups, active incentives, production subsidies, and wholesaler partnerships. The ISM method is used to identify priorities, including government coordination and improvement of field officers and farmers.